Respuesta :
Answer:
[tex]y = C_1J_2(3\sqrt{x})+C_2Y_2(3\sqrt{x})[/tex]
Step-by-step explanation:
[tex]x^{2} \dfrac{d^2 y}{dx^2} + x\dfrac{dx}{dy} + (x-1)y =0[/tex]
Considering [tex]x=0[/tex] ordinary point we could use Frobenius method assuming
[tex]$y = \sum_{n=0}^{\infty} c_nx^n$[/tex]
and consider the series representation given by the method to solve the equation. I think this way is harder.
In your case, It seems to have something to do with Bessel differential equation
[tex]x^2 y'' + x y' + (x^2-n^2) y = 0[/tex]
that will have the same representation as the Frobenius method. To get the form [tex](x^2-n^2)[/tex] as we have [tex] (x-1)[/tex] in the given equation we can substitute [tex]x[/tex] and take [tex]x = \dfrac{t^2}{9}[/tex]
Thus,
[tex]\dfrac{dy}{dx} = \dfrac{3}{t}\dfrac{dy}{dt} \implies \dfrac{d^2y}{dx^2} = \dfrac{9}{t^2}\dfrac{d^2y}{dt^2}-\dfrac{9}{t^3}\dfrac{dy}{dt} [/tex]
[tex]$\implies \frac{1}{3^2}\left(t^2\frac{{d}^2y}{{d}t^2}+t\frac{{d}y}{{d}t}+(t^2-3^2)y\right) = 0$[/tex]
The solution will have the format
[tex]y( x) = {C_1}{J_n}( x) + {C_2}{Y_n}( x )[/tex]
such that
[tex]${J_n}( x ) = \sum\limits_{p = 0}^\infty {\frac{{{{( { - 1} )}^p}}}{{\Gamma ( {p + 1} )\Gamma ( {p + n + 1} )}} {{\left( {\frac{x}{2}} \right)}^{2p + n}}}$ [/tex]
[tex]${Y_n}\left( x \right) = \frac{{{J_n}\left( x \right)\cos \pi n - {J_{ - n}}\left( x \right)}}{{\sin \pi n}}$ [/tex]
and [tex]C_1, C_2[/tex] are constants
And the order of the Bessel equation is [tex]n=2[/tex]
In our case, we can just write
[tex]y(t) = C_1J_2(t)+C_2Y_2(t)[/tex]
[tex]y = C_1J_2(3\sqrt{x})+C_2Y_2(3\sqrt{x})[/tex]